ADJEKTIVA BAHASA DAYAK BENUAQ DI KAMPUNG LAMBING KECAMATAN MUARA LAWA KABUPATEN KUTAI BARAT - Pey, Adeliana Chein; Hanum, Irma Surayya; Wahyuni, Ian (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
. This study aims to (1) describe the adjective form of the Dayak Benuaq language in Lambing Village, Muara Lawa District, West Kutai Regency, (2) describe the function of the Benuaq Dayak language adjective in Lambing Village, Muara Lawa District, West Kutai Regency. This type of research is field research. The data in this study is in the form of speech. Sources of data in this study, namely the utterances spoken by three informants. The data collection technique used was observation technique, refer to conversational engagement, note-taking and tapping techniques. The technique of analyzing qualitative descriptive data is by using the distributional method. The results of this study based on the form found that there are two parts, namely, monomorphemic adjectives and polymorphemic adjectives. Based on the function of the adjective, it was found that there are three parts, namely the attributive function is a delimiter in a noun phrase where the noun can be the subject, object, and complement, the predicative function is a predicate or complementary function in a clause, and the adverbial function or description is not a core element. in a sentence.